2019
DOI: 10.1177/2325967119849035
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Sprain Versus Muscle Strain Injury in Professional Men’s Basketball: A 9-Year Prospective Follow-up Study

Abstract: Background: Ankle sprain is the most common injury in basketball players. However, in our routine clinical evaluation, we observe a high frequency of muscle injury. Currently, no reliable information is available regarding the magnitude of these types of injury. Purpose: To describe the type and rate of muscle injuries in male basketball players and discuss clinical management and prevention strategies. Study Design: Descriptive epidemiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
1
18
0
2
Order By: Relevance
“…In the first prospective study on a European count throughout the 32-week season Cumps et al (2007) reported incidence rate of 8.0 injuries/1000h for men and 13.9/1000h for women. Another European study (Rodas, et al, 2019) with professional male basketball players reported that the general injury rate over nine seasons was 10.8 injuries per 1000 player-hours (95% CI, 9.9-11.9). These studies showed a higher incidence rate of injuries, which might be due to the limitation in our methodology and big influence of recall bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first prospective study on a European count throughout the 32-week season Cumps et al (2007) reported incidence rate of 8.0 injuries/1000h for men and 13.9/1000h for women. Another European study (Rodas, et al, 2019) with professional male basketball players reported that the general injury rate over nine seasons was 10.8 injuries per 1000 player-hours (95% CI, 9.9-11.9). These studies showed a higher incidence rate of injuries, which might be due to the limitation in our methodology and big influence of recall bias.…”
Section: Resultsmentioning
confidence: 99%
“…Moderate injuries represented the most frequent type of injury (41%) in the study by Passanen et al (2017) as well. Lower extremity injuries are the most common injuries in basketball accounting for up to 90% of all injuries (90% in Rodas, et al, 2019;88% in Owoeye, et al, 2020;78% in Pasanen, et al, 2017;73% in Baker, et al, 2020;55 and 67% in Zuckermann, et al, 2018;65% in Deitch, et al, 2006;65% in Andreoli, et al, 2018;62% in Drakos, et al, 2010). Results in our study, where lower extremity injuries accounted for 80% of all the injuries, are also in the reported interval.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from the NCAA 1 ) indicated that the GIR (13.79/1000 PH) was significantly higher than the PIR (3.98/1000 PH), which is consistent with the findings of our study. Rodas et al 6 ) reported that the total IR in the Spanish league was 10.8/1000 PH (GIR, 76.4/1000 PH; PIR 7.1/1000 PH), injuries that caused players to be absent from game or practice were 4.8/1000 PH, and injuries that only needed medical attention were 4.0/1000 PH. This result was considerably higher than ours (GIR 47.16/1000 PH; PIR 1.50/1000 PH).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle injuries are common in many sports, such as basketball [1], rugby [2], football [3], tennis [4], track and field [5]. Muscle injury can represent more than 40% of total injuries in football [3,6], and track and field [5].…”
Section: Introductionmentioning
confidence: 99%